Physicochemical Characterization of a Co-Amorphous Atorvastatin-Irbesartan System with a Potential Application in Fixed-Dose Combination Therapy - Marcin Skotnicki; Barbara Jadach; Agnieszka Skotnicka; Bartłomiej Milanowski; Lidia Tajber; Marek Pyda; Jacek Kujawski (MDPI AG, 2021)
The aim of this study was to characterize a 1:1 molar ratio of a pharmacologically relevant co-amorphous atorvastatin-irbesartan (ATR-IRB) system obtained by quench cooling of the crystalline ATR/IRB physical mixture for potential use in the fixed-dose combination therapy. The system was characterized by employing standard differential scanning calorimetry (DSC), Fourier transform-infrared spectroscopy (FT-IR), and intrinsic dissolution rate studies. Quantum mechanical calculations were performed to obtain information regarding intermolecular interactions in the studied co-amorphous ATR-IRB system. The co-amorphous formulation showed a significant improvement in the intrinsic dissolution rate (IDR) of IRB over pure crystalline as well as its amorphous counterpart. An unusual behavior was observed for ATR, as the IDR of ATR in the co-amorphous formulation was slightly lower than that of amorphous ATR alone. Short-term physical aging studies of up to 8 h proved that the ATR-IRB co-amorphous system remained in the amorphous form. Furthermore, no physical aging occurred in the co-amorphous system. FT-IR, density functional theory calculations, and analysis of Tg value of co-amorphous system using the Couchman-Karasz equation revealed the presence of molecular interactions between APIs, which may contribute to the increased physical stability.